Estimation of genetic parameters for fertility traits in Chinese Holstein of south China - Zhu, Kai; Li, Tuowu; Liu, Dengying; Wang, Shiyi; Wang, Sihu; Wang, Qishan; Pan, Yuchun; Zan, Linsen; Ma, Peipei (Frontiers in Genetics, 2024)
Chinese Holstein in South China suffers heat stress in a long period, which leads to evolution differently to Chinese Holstein in North China. The aim of this study was to estimate genetic parameters of fertility traits for Chinese Holstein in South China. A total of 167,840 Chinese Holstein heifers and cows from Guangming Animal Husbandry Co., LTD farms were used in this study. The fertility traits analyzed were calving interval (CI), days open (DO), age of first service (AFS), age of first calving (AFC), calving to first insemination (CTFS), first insemination to conception (FSTC), gestation length (GL), non-return rate to 56 days (NRR), and number of services (NS). The descriptive statistics revealed that the same trait in heifer performed better than in cow, which was consistent with the other studies. The heritabilities of fertility traits in this study ranged from close to This is a provisional file, not the final typeset article 0 (for NS of cow) to 0.2474 (for AFC of heifer). The genetic correlation of NRR between heifer and cow was 0.9993, which indicated that the NRR for heifer and cow could be treated as one trait in this population. Therefore, the heritability of NRR for heifer could be improved significantly when twotrait model was applied. The results in this study could provide genetic parameters for the animal breeding program of Chinese Holstein in the south of China.